Comparison of VO2peak and achievement of VO2peak criteria in three modes of exercise in female triathletes - Snoza, C. T.; Berg, K. E.; Slivka, D. R. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to compare peak aerobic capacity in female triathletes in 3 modes of exercise: treadmill, cycle, and arm ergometer. A second purpose was to determine the extent that physiologic criteria for achieving VO2peak were reached in each mode of exercise. Six criteria were examined: VO2 plateau, heart rate (HR), blood lactate concentration (BLC), respiratory exchange ratio, oxygen saturation, and rating of perceived exertion (RPE). Twelve recreational level female triathletes completed maximal tests on the treadmill, stationary bike, and arm ergometer. Results indicated VO2peak (ml/kg/min) is highest on a treadmill (46.8 ± 2.1), intermediate in cycling (40.7 ± 5.0), and lowest in arm ergometry (28.2 ± 3.3) with mean differences being significant (p = 0.05). Blood lactate concentration and RPE criteria were met by the highest number of subjects across the 3 modes of testing while the HR criterion was not achieved in any participant in arm ergometry and only 2 in cycling. It was concluded that in moderately trained recreational level triathletes, VO2peak is highest in running and lowest in arm ergometry. Criteria for achieving VO2peak most frequently were blood lactate level and RPE. Coaches and researchers should appreciate that VO2peak values of moderately trained triathletes differ considerably in contrast to elite triathletes and tend to be highest on the treadmill and lowest in arm ergometry. Also, criteria used to determine achievement of VO2peak should be carefully selected and seem to be best achieved using BLC and RPE.